Differentiating Drug‐Induced Multichannel Block on the Electrocardiogram: Randomized Study of Dofetilide, Quinidine, Ranolazine, and Verapamil. Issue 5 (23rd July 2014) - Johannesen, L; Vicente, J; Mason, J W; Sanabria, C; Waite‐Labott, K; Hong, M; Guo, P; Lin, J; Sørensen, J S; Galeotti, L; Florian, J; Ugander, M; et al.
<x xml:space="preserve">Abstract</x> Block of the hERG potassium channel and prolongation of the QT interval are predictors of drug‐induced torsade de pointes. However, drugs that block the hERG potassium channel may also block other channels that mitigate torsade risk. We hypothesized that the electrocardiogram can differentiate the effects of multichannel drug block by separate analysis of early repolarization (global J–Tpeak) and late repolarization (global Tpeak–Tend). In this prospective randomized controlled clinical trial, 22 subjects received a pure hERG potassium channel blocker (dofetilide) and three drugs that block hERG and either calcium or late sodium currents (quinidine, ranolazine, and verapamil). The results show that hERG potassium channel block equally prolongs early and late repolarization, whereas additional inward current block (calcium or late sodium) preferentially shortens early repolarization. Characterization of multichannel drug effects on human cardiac repolarization is possible and may improve the utility of the electrocardiogram in the assessment of drug‐related cardiac electrophysiology. Clinical Pharmacology & Therapeutics (2014); 96 5, 549–558. doi:10.1038/clpt.2014.155